Perilaku Religiusitas Komunitas Muslim Timor Leste Pasca Konversi Agama di Sumedang - Pahlawan Gowal (TEMALI : Jurnal Pembangunan Sosial, 2020)
This article discusses the religious behavior of the converts coming from a particular religious community to another. This study aimed to determine the factors causing religious conversion and religious behavior after religious conversion. The research method used is a case study, data sources obtained from informants through in-depth interviews, observations, and literature review. The study results found that the religious conversion of the Timor Leste Muslim community was caused by family factors and the environment in which they lived (YALTIM institution). Post-religious conversion behavior has developed, such as carrying out obligatory prayers and Sunnah, reading the Koran, praying, dhikr, and fasting obligatory and Sunnah. They also believe in Allah's existence, the prophets, messengers, angels, heaven, and hell. Moreover, they feel comfortable when carrying out religious orders.